Taşınmaz Kültür Varlıklarının Belgelendirilmesinde Jeomekansal Veri/bilgi Yönetimi - Kıvılcım, Cemal Özgür (Fen Bilimleri Enstitüsü, 2009)
Çeşitli nedenlerle zaman içinde yıpranan taşınmaz kültür varlıklarının nesnel temellere dayanan hızlı ve doğru belgelendirme çalışmalarıyla yaşatılması mümkündür. Taşınmaz kültür varlıklarını belgelendirme çalışmalarında, modern jeomekansal veri toplama tekniklerine dayanan belgelendirme uygulamaları ve mekansal bilgi sistemleri denemeleri yaygınlaşmaktadır. Bu tez çalışmasında, taşınmaz kültür varlıklarına ilişkin jeomekansal veri/bilgi toplanmasında en uygun tekniklerin seçimi, çalışmaların planlanması, elde edilen veri ve bilginin mekansal bilgi sistemlerine aktarımı konuları araştırılmıştır. Tarihi çevre koruma çalışmalarında yürütülen farklı rölöve, restitüsyon ve restorasyon projelerinde ihtiyaç duyulan jeomekansal veri ve bilgi türleri irdelenerek, tasarım ve yönetim ilkeleri belirlenmiştir. Geomatik Mühendislerinin, çok disiplinli çalışmalar olarak yürütülen taşınmaz kültür varlıklarını koruma projelerinde sağlayabilecekleri katkılar değerlendirilmiştir.

Cultural heritage structures get severe damages during the time. In order to preserve them, fast and accurate documentation of structures and their surrounded areas based on scientific techniques are extremely needed. The technological developments in the recent years provided that human activities and products can be simulated in virtual three dimensional environments with temporal changes, all built on geospatial data infrastructures. More, with various interfaces and visualization techniques via the Internet, sharing such data and information in interactive worlds has significantly increased. In this thesis; work planning, use and optimization of techniques to acquire geospatial data, acquiring geospatial data/information and handling them in spatial information systems are researched for cultural heritage documentation projects. The necessary design and management principles from geospatial data/information aspects are presented from different examined architectural survey, restitution and restoration works. The significant benefits and possible contributions of Geomatics Engineers in acquiring/managing geospatial data and information are evaluated for multidiscipline cultural heritage documentation works.
Geospatial Data/information Management For Cultural Heritage Management
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: Taşınmaz Kültür Varlıkları; Jeomekansal Veri/Bilgi Yönetimi; Kültür Varlıklarının Belgelendirilmesi; Tarihi Çevre Koruma; Cultural Heritage Properties; Geosptatial Data/Information Management; Cultural Heritage Documentation; Historical Sites Protection